Adverse perinatal outcomes in immigrants: A ten‐year population‐based observational study and assessment of growth charts. Issue 6 (2nd September 2019) - Choi, Stephanie K. Y.; Henry, Amanda; Hilder, Lisa; Gordon, Adrienne; Jorm, Louisa; Chambers, Georgina M.
Abstract: Background: Maternity populations are becoming increasingly multiethnic. Conflicting findings exist regarding the risk of adverse perinatal outcomes among immigrant mothers from different world regions and which growth charts are most appropriate for identifying the risk of adverse outcomes. Objective: To evaluate whether infant mortality and morbidity, and the categorisation of infants as small for gestational age or large for gestational age (SGA or LGA) vary by maternal country of birth, and to assess whether the choice of growth chart alters the risk of adverse outcomes in infants categorised as SGA and LGA. Methods: A population cohort of 601 299 singleton infants born in Australia to immigrant mothers was compared with 1.7 million infants born to Australian‐born mothers, 2004‐2013. Infants were categorised as SGA and LGA according to a descriptive Australian population‐based birthweight chart (Australia‐2012 reference) and the prescriptive INTERGROWTH‐21st growth standard. Propensity score reweighting was used for the analysis. Results: Compared to Australian‐born infants, infants of mothers from Africa, Philippines, India, other Asia countries, and the Middle East had between 15.4% and 48.1% elevated risk for stillbirth, preterm delivery, or low Apgar score. The association between SGA and LGA and perinatal mortality varied markedly by growth chart and country of birth. Notably, SGA infants from African‐born mothers had a relative risk of perinatal mortality of 6.1 (95% CI 4.3, 6.7) and 17.3 (95% CI 12.0, 25.0) by the descriptive and prescriptive charts, respectively. LGA infants born to Australian‐born mothers were associated with a 10% elevated risk of perinatal mortality by the descriptive chart compared to a 15% risk reduction by the prescriptive chart. Conclusions: Country‐of‐birth‐specific variations are becoming increasingly important for providing ethnically appropriate and safe maternity care. Our findings highlight significant variations in risk of adverse perinatal outcomes in immigrant subgroups, and demonstrate how the choice of growth chart alters the quantification of risk associated with being born SGA or LGA.